Complex partial status epilepticus associated with cyclosporin A therapy. Issue 9 (September 1989) - Appleton, R E; Farrell, K; Teal, P; Hashimoto, S A; Wong, P K
Abstract : Significant neurotoxicity including seizures, encephalopathy and coma may complicate the use of cyclosporin A (CyA). Two patients are described, receiving CyA, who presented with abnormal behaviour, stupor, focal motor activity and were shown to be in complex partial status epilepticus (CPSE). Abnormalities of behaviour and/or stupor in patients receiving CyA may be a manifestation of CPSE. Patients receiving CyA who develop an encephalopathy should have electroencephalography performed at the time of the abnormal behaviour.